2020
DOI: 10.3390/ijms21072414
|View full text |Cite
|
Sign up to set email alerts
|

Development and Proof-of-Concept Application of Genome-Enabled Selection for Pea Grain Yield under Severe Terminal Drought

Abstract: Terminal drought is the main stress limiting pea (Pisum sativum L.) grain yield in Mediterranean environments. This study aimed to investigate genotype × environment (GE) interaction patterns, define a genomic selection (GS) model for yield under severe drought based on single nucleotide polymorphism (SNP) markers from genotyping-by-sequencing, and compare GS with phenotypic selection (PS) and marker-assisted selection (MAS). Some 288 lines belonging to three connected RIL populations were evaluated in a manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…Results were averaged across repetitions, sets of training environments and RIL populations. This analysis was initially exploited to define the optimal thresholds of missing data per marker (mpm) and missing data per sample (mps) by employing the Ridge regression BLUP (rrBLUP) model (Meuwissen et al, 2001), which combined high computation ability with good prediction ability in early studies (Annicchiarico et al, 2019(Annicchiarico et al, , 2020. We envisaged intra-population, interenvironment predictions according to four possible GS models, namely, rrBLUP, Bayesian C, Bayesian A, and Bayesian Lasso (Meuwissen et al, 2001;Park and Casella, 2008).…”
Section: Genomic Regression Models and Data Configurationsmentioning
confidence: 99%
“…Results were averaged across repetitions, sets of training environments and RIL populations. This analysis was initially exploited to define the optimal thresholds of missing data per marker (mpm) and missing data per sample (mps) by employing the Ridge regression BLUP (rrBLUP) model (Meuwissen et al, 2001), which combined high computation ability with good prediction ability in early studies (Annicchiarico et al, 2019(Annicchiarico et al, , 2020. We envisaged intra-population, interenvironment predictions according to four possible GS models, namely, rrBLUP, Bayesian C, Bayesian A, and Bayesian Lasso (Meuwissen et al, 2001;Park and Casella, 2008).…”
Section: Genomic Regression Models and Data Configurationsmentioning
confidence: 99%
“…Its cost-efficient application to plant breeding has greatly been enhanced by recent sequencing techniques, such as genotyping-by-sequencing (GBS; Elshire et al, 2011 ), that allow large germplasm sets to be genotyped by thousands of single nucleotide polymorphism (SNP) markers at a relatively low cost. Pioneer studies for pea suggested greater genetic gain per unit time of genomic over phenotypic selection for improving grain yield under PS conditions in moisture-favorable (Annicchiarico et al, 2019b ) and severely drought-prone target regions (Annicchiarico et al, 2020 ). Genomic selection out-performed phenotypic selection in breeding for intercropping in a study based on stochastic simulation data (Bančič et al, 2021 ), but no experimental assessment of the value of genomic selection for intercropping is available.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneer studies highlighted greater predicted yield gain per unit time or unit cost for alfalfa ( Annicchiarico et al, 2015b ), soybean ( Matei et al, 2018 ), and pea ( Annicchiarico et al, 2019b ). In legumes, GS displayed convenient predictive ability also for key grain quality ( Stewart-Brown et al, 2019 ) or forage quality traits ( Biazzi et al, 2017 ; Pégard et al, 2021 ) and emerging complex traits, such as drought tolerance ( Li et al, 2019 ; Annicchiarico et al, 2020 ), performance in intercropping ( Annicchiarico et al, 2021 ), and tolerance to some biotic stresses ( Carpenter et al, 2018 ). However, research work is crucially needed to fully assess the potential of GS for different legume species and target traits, explore the transferability of its models to different breeding populations, and optimize its adoption within the breeding schemes.…”
Section: Novel Techniques To Enhance the Selection Efficiency And Ease The Complexity Of Selectionmentioning
confidence: 99%